In vitro-Formulated Oligomers of Strep-Tagged Avian Influenza Haemagglutinin Produced in Plants Cause Neutralizing Immune Responses - Phan, Hoang Trong; Gresch, Ulrike; Conrad, Udo (Frontiers in Bioengineering and Biotechnology, 2018)
The worldwide emergence of the novel influenza A H5N1 and H5N8 has notably and directly impacted the poultry industry, resulting in the need for effective and cheap vaccination strategies to protect poultry worldwide. Subunit vaccines from plants can be produced for a low cost, and plant production systems are easily scaled up at low infrastructure cost. However, subunit vaccines generally induce low immunogenicity against influenza. To address this issue, we present a new and innovative method to generate highly immunogenic H5 oligomers. The method is based on specific and high-affinity interaction between engineered streptavidin (Strep-Tactin® XT) and the Strep-tag II peptide. H5-Strep-tag II-tagged trimers were produced via transient agroinfection in tobacco leaves and purified, and oligomers were formulated in vitro by adding purified homotetrameric Strep-Tactin® XT. Immunogenicity was tested by performing mouse immunizations. Haemagglutinin oligomers produced in vitro by combining Strep-Tactin® XT and Strep-tag II-fused haemagglutinin trimers from plants raised potentially neutralizing antibodies in mice. Vaccines based on actual H5N1 haemagglutinin can be produced by combining strep-tagged haemagglutinin trimers from plants and Strep-Tactin® XT.